Survival after cytoreductive surgery for peritoneal metastases in colorectal cancer patients: Does a history of resected liver metastases worsen the prognosis?. Issue 4 (April 2022) - Dumont, Frédéric; Guénolé, Simon; Loaec, Cécile; Bourgin, Charlotte; Raimbourg, Judith; Senellart, Hélène; Hiret, Sandrine; Doucet, Ludovic; Raoul, Jean-Luc; Thibaudeau, Emilie
Abstract: Background: Nowadays, resection of two (liver and peritoneum) concomitant colorectal cancer metastatic sites is no longer contraindicated. However, the oncologic outcomes of resecting peritoneal metastases (PM) occurring more than six months after resection of liver metastases (LM) are unknown. Aim: The aim of this study was to compare patients with complete cytoreductive surgery (CRS) with or without a history of previous liver resection (LR). Methods: Analysis from a prospective database of 74 patients with metachronous PM treated with CRS between 2010 and 2020. Results: All patients had PM metachronous to primary, 64 patients underwent CRS alone (CRSa) and 10 CRS more than six months after LR (LR-CRS). There was no statistical difference between the groups for clinical or therapeutic characteristics. There were more signet ring cell/mucinous adenocarcinomas in the CRSa group than in the LR-CRS group (19% vs. 0%, p = 0.049). The median peritoneal cancer index (PCI) was 4 and 6 (p = 0.749) in the LR-CRS and CRSa groups, respectively. Median overall survival (OS) and disease-free survival (DFS) were not statistically different between the two groups with 43.6 and 13 months for the CRSa group and 31.1 months and 9.4 months for LR-CRS. Advanced age was an independent negative prognostic factor for OS and high PCI was limit significant. No prognostic factor for DFS was found. Conclusions: LR before CRS has no major prognostic impact. Resection of iterative liver and peritoneum metastases can achieve long-term survival.